Nitrate retention in a variable-charge soil, as influenced by phosphate fertilizing and liming - Dynia, José Flavio; Camargo, Otávio Antônio de (Pesquisa Agropecuaria Brasileira, 1999)
The effects of phosphorus application, and liming, were evaluated as affecting the nitrate retention capacity (NRC) of a variable charge soil. A clayey dark-red latosol (oxisol) from the "cerrado" region was planted with corn, wheat, rice and dry bean (2, 4, 5 and 6 crops, respectively) between 1982 and 1989. In this period the soil was treated with phosphate (1530 kg/ha of P2O5: 90 kg/ha per crop), or phosphate (1530 kg/ha of P2O5)+lime (5.5 t/ha of dolomitic limestone: 2.5 and 3.0 t/ha, applied in 1982 and 1985, respectively). Soil samples collected in 1991 from plots which had received these treatments, and from one with no treatment, were tested for NRC. The results showed a negative NRC (exclusion of the anion) in the plow layer (0-20 cm), and a positive NRC which increased with depth, in the 20-60 cm layer. Both treatments reduced the original NRC of the soil in the 20-60 cm layer, but the effect of lime was much more pronounced than that of phosphate. Phosphate fertilizing, and, specially, liming, exerted a considerable residual effect on the NRC of the soil.